2018
DOI: 10.3390/agronomy8090160
|View full text |Cite
|
Sign up to set email alerts
|

Improving Flooding Tolerance of Crop Plants

Abstract: A major problem of climate change is the increasing duration and frequency of heavy rainfall events. This leads to soil flooding that negatively affects plant growth, eventually leading to death of plants if the flooding persists for several days. Most crop plants are very sensitive to flooding, and dramatic yield losses occur due to flooding each year. This review summarizes recent progress and approaches to enhance crop resistance to flooding. Most experiments have been done on maize, barley, and soybean. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 206 publications
(219 reference statements)
0
57
0
Order By: Relevance
“…The interactive effects between two stresses are related to morphological adaptation and hormonal regulation [12]; when plants are subjected to flood followed by drought, their morphological and physiological adaptive response to the preceding flood probably enhances their tolerance to the subsequent drought. The most promising flood-adaptive strategy for plants is to form aerenchyma and adventitious roots to extract more soil oxygen [46], and cotton also exhibits this strategy [33]. In addition, cotton root vigor recovered after flood and even surpassed that in the unstressed treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…The interactive effects between two stresses are related to morphological adaptation and hormonal regulation [12]; when plants are subjected to flood followed by drought, their morphological and physiological adaptive response to the preceding flood probably enhances their tolerance to the subsequent drought. The most promising flood-adaptive strategy for plants is to form aerenchyma and adventitious roots to extract more soil oxygen [46], and cotton also exhibits this strategy [33]. In addition, cotton root vigor recovered after flood and even surpassed that in the unstressed treatment [20].…”
Section: Discussionmentioning
confidence: 99%
“…Increased coastal flooding and changes of annual precipitation are predicted to cause significant economic losses within the next century (Hirabayashi et al, 2013). To aid in mitigating the future economic impact of flooding damage on plants, significant research has been conducted in the field of crop improvement with regards to understanding plant adaptations to water immersion (Grover et al, 2000;Evans, 2004;Bailey-Serres et al, 2012;Valliyodan et al, 2016;Mustroph, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…aerenchyma, Dennis et al, 2000), as supported by the findings of Pampana et al (2016) who reported a reduction of grain yield of two varieties (Claudio and Svevo) only when waterlogging was prolonged for more than 20 days. Although O 3 and flooding are similarly able to induce oxidative stress in plants (Mustroph, 2018;Sandermann, 1996), our data show that the phenolic response to these environmental constraints is stress specific, with a higher activation induced under O 3 than under flooding, another aspect to take into account when breeding future cultivars.…”
Section: Discussionmentioning
confidence: 70%
“…In most of these areas, durum wheat have commonly to cope with major climatic constraints, mainly elevated temperatures, drought and high O 3 levels, but also flooding (this is expected to increase in the near future). Most of available literature concerns O 3 effects on common wheat (T. aestivum L.), although durum wheat is also known to be both O 3 (Fangmeier, Brockerhoff, Grüters, & Jäger, 1994;Ollerenshaw & Lyons, 1999;Picchi, Francini, Nali, & Lorenzini, 2006) and flooding sensitive (Burgos, Stamp, & Schmid, 2001;Pampana, Masoni, & Arduini, 2016), even if somewhat contrasting results have been reported based on genotypic differences in tolerance and on intensity and duration of the stress exposure (Gerosa et al, 2014;Mustroph, 2018;Pampana et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation